Items of Reading Test and Construction of a Diagnostic Reading Test in Kannada - G, Purushothama (Journal of All India Institute of Speech and Hearing)
Some diagnostic reading tests in English were analyzed. The test items were categorized and the literature is reviewed. Also presented is the outcome of research on the related concepts of test items. The important factors for testing reading are identified. Kannada material for diagnostic testing is presented with details of testing, interpretation and usage.